Dynamics of sputum conversion during effective tuberculosis treatment: A systematic review and meta-analysis. - Claire J Calderwood; James P Wilson; Katherine L Fielding; Rebecca C Harris; Aaron S Karat; Raoul Mansukhani; Jane Falconer; Malin Bergstrom; Sarah M Johnson; Nicky McCreesh; Edward J M Monk; Jasantha Odayar; et al. (PLoS Medicine)
Background Two weeks' isolation is widely recommended for people commencing treatment for pulmonary tuberculosis (TB). The evidence that this corresponds to clearance of potentially infectious tuberculous mycobacteria in sputum is not well established. This World Health Organization-commissioned review investigated sputum sterilisation dynamics during TB treatment. Methods and findings For the main analysis, 2 systematic literature searches of OvidSP MEDLINE, Embase, and Global Health, and EBSCO CINAHL Plus were conducted to identify studies with data on TB infectiousness (all studies to search date, 1 December 2017) and all randomised controlled trials (RCTs) for drug-susceptible TB (from 1 January 1990 to search date, 20 February 2018). Included articles reported on patients receiving effective treatment for culture-confirmed drug-susceptible pulmonary TB. The outcome of interest was sputum bacteriological conversion: the proportion of patients having converted by a defined time point or a summary measure of time to conversion, assessed by smear or culture. Any study design with 10 or more particpants was considered. Record sifting and data extraction were performed in duplicate. Random effects meta-analyses were performed. A narrative summary additionally describes the results of a systematic search for data evaluating infectiousness from humans to experimental animals (PubMed, all studies to 27 March 2018). Other evidence on duration of infectiousness-including studies reporting on cough dynamics, human tuberculin skin test conversion, or early bactericidal activity of TB treatments-was outside the scope of this review. The literature search was repeated on 22 November 2020, at the request of the editors, to identify studies published after the previous censor date. Four small studies reporting 3 different outcome measures were identified, which included no data that would alter the findings of the review; they are not included in the meta-analyses. Of 5,290 identified records, 44 were included. Twenty-seven (61%) were RCTs and 17 (39%) were cohort studies. Thirteen studies (30%) reported data from Africa, 12 (27%) from Asia, 6 (14%) from South America, 5 (11%) from North America, and 4 (9%) from Europe. Four studies reported data from multiple continents. Summary estimates suggested smear conversion in 9% of patients at 2 weeks (95% CI 3%-24%, 1 single study [N = 1]), and 82% of patients at 2 months of treatment (95% CI 78%-86%, N = 10). Among baseline smear-positive patients, solid culture conversion occurred by 2 weeks in 5% (95% CI 0%-14%, N = 2), increasing to 88% at 2 months (95% CI 84%-92%, N = 20). At equivalent time points, liquid culture conversion was achieved in 3% (95% CI 1%-16%, N = 1) and 59% (95% CI 47%-70%, N = 8). Significant heterogeneity was observed. Further interrogation of the data to explain this heterogeneity was limited by the lack of disaggregation of results, including by factors such as HIV status, baseline smear status, and the presence or absence of lung cavitation. Conclusions This systematic review found that most patients remained culture positive at 2 weeks of TB treatment, challenging the view that individuals are not infectious after this interval. Culture positivity is, however, only 1 component of infectiousness, with reduced cough frequency and aerosol generation after TB treatment initiation likely to also be important. Studies that integrate our findings with data on cough dynamics could provide a more complete perspective on potential transmission of Mycobacterium tuberculosis by individuals on treatment. Trial registration Systematic review registration: PROSPERO 85226.